2023
DOI: 10.1371/journal.pone.0293848
|View full text |Cite|
|
Sign up to set email alerts
|

Development and initial validation of the Orthotic Patient-Reported Outcomes—Mobility (OPRO-M): An item bank for evaluating mobility of people who use lower-limb orthoses

Geoffrey S. Balkman,
Alyssa M. Bamer,
Phillip M. Stevens
et al.

Abstract: Lower limb orthoses (LLOs) are externally-applied leg braces that are designed to improve or maintain mobility in people with a variety of health conditions that affect lower limb function. Clinicians and researchers are therefore often motivated to measure LLO users’ mobility to select or assess the effectiveness of these devices. Patient-reported outcome measures (PROMs) can provide insights into important aspects of a LLO user’s mobility for these purposes. However, few PROMs are available to measure mobili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Device use data were collected as part of a study that aimed to develop a novel patient-reported item bank for measuring orthotic mobility. 10 Eligible individuals included adults with chronic functional or structural lower limb impairments who reported using a LLO on one or both legs for at least 6 months. For the purposes of this study, LLOs were limited to orthoses that extended proximally from the foot to a level above the ankle, including ankle-foot orthoses (AFOs), knee-ankle-foot orthoses (KAFOs), and hip-knee-ankle-foot orthoses (HKAFOs).…”
Section: Methodsmentioning
confidence: 99%
“…Device use data were collected as part of a study that aimed to develop a novel patient-reported item bank for measuring orthotic mobility. 10 Eligible individuals included adults with chronic functional or structural lower limb impairments who reported using a LLO on one or both legs for at least 6 months. For the purposes of this study, LLOs were limited to orthoses that extended proximally from the foot to a level above the ankle, including ankle-foot orthoses (AFOs), knee-ankle-foot orthoses (KAFOs), and hip-knee-ankle-foot orthoses (HKAFOs).…”
Section: Methodsmentioning
confidence: 99%